Learning to Unlearn White Supremacist Consciousness - Carole Barlas; Elizabeth Kasl; Roberta Kyle; Alec MacLeod; Doug Paxton; Penny Rosenwasser; Linda Sartor (Adult Education Research Conference, 2000)
Using cooperative inquiry as a self-directed learning strategy, people of European-American descent learn to unlearn white supremacist consciousness. Facilitators of changed thinking and behavior include relationships of trust in the all-white inquiry groups and relationships with people of color in participants' daily lives.